Outcome measures used in patient with knee osteoarthritis: With special importance on functional outcome measures - Samuel, Asir John; Kanimozhi, Durairaj (International Journal of Health Sciences, 2018)
Understanding the impact of evidence-based practice toward the rehabilitation of patients with knee osteoarthritis (PKOA) is possible with appropriate outcome measures. There is a definite need to summarize the available outcomes with reference to knee OA. This review summarizes the available outcome measures used in the diagnosis, prognosis, and rehabilitation of PKOA. Electronic searches of PubMed, Medline, CINAHL, PsycINFO, Google Scholar, and EBSCO were conducted using terms relating to outcome measures used in the diagnosis, prognosis, and rehabilitation of PKOA. Papers examining the relationship between psychosocial factors and pain and disability outcomes following physiotherapy were included. Two reviewers selected, appraised and extracted studies independently.The searched papers were classified under three classifications, radiological, arthroscopic, and functional knee OA outcome measures. 26 outcome measures used in the diagnosis, prognosis, and rehabilitation of PKOA were identified. Nine outcome measures were included under radiological, four under arthroscopic and remaining 13 under functional classification. Oxford knee score and WOMAC have excellent reliability and good validity among them. In developing countries, still, we use the scales validated and available from the developed countries. This will not reflect the actual treatment effect among PKOA. This review will assist in educating orthopedician, physiotherapist, academician, and researchers on the available in the diagnosis, prognosis, and rehabilitation of PKOA. This review highlight the need for patient-reported outcome measures from the developing countries to document actual treatment effect.